Educational actions in high-risk prenatal care for pregnant women with heart disease: strategies for efficient self-care (Research, Society and Development, 2020)
In Brazil, the incidence of heart disease in pregnancy reaches a rate of 4.2% among pregnant women, a number eight times higher than the international statistics reported in the study by the European Society of Cardiology. Therefore, the health and well-being of pregnant women with heart disease must be monitored and the pathology diagnosed early to reduce the risk of life in the maternal-fetal binomial. Thus, the objective was to report an experience of nursing students about an action of health education for pregnant women with heart disease, in addition to promoting health in a safe way, encouraging self-care and well-being. It is a descriptive study, with a qualitative approach, of the experience report type, in which it seeks to understand the relationships developed based on different contexts. It was based on the methodology of problematizing the Arch of Charles Maguerez. Thus, as the main results achieved, it was evident in the present study that health education as a teaching methodology during high-risk prenatal care obtained satisfactory results, since it promoted the exchange of information and the transfer of knowledge, while fostering autonomy and self-management of health effectively among pregnant women with heart disease. Finally, it appears that the participation of students in these activities made it possible to obtain skills and competences for the future profession, as well as greater interaction with the community.